2022
DOI: 10.1155/2022/1248990
|View full text |Cite
|
Sign up to set email alerts
|

Shape Approximation and Size Difference of the Upper Part of the Talus: Implication for Implant Design of the Talar Component for Total Ankle Replacement

Abstract: The implant design of the talar component for total ankle replacement (TAR) should match the surface morphology of the talus so that the replaced ankle can restore the natural motion of the tibiotalar joint and may reduce postoperative complications. The purpose of this study was to introduce a new 3D fitting method (the two-sphere fitting method of the talar trochlea with three fitting resection planes) to approximate the shape of the upper part of the talus for the Chinese population. 90 models of the tali f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Clinically, it is well established that male generally has a bigger size of talus than female. 4,32 However, it is noted that at the bottom of the talar head, the mean shape of the female tali extrudes which means that its talar head has a large top-bottom thickness and is therefore more plantar flexed. Therefore, we do not consider the average female shape to be geometrically similar to the average male shape as Liu et al 29 claimed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, it is well established that male generally has a bigger size of talus than female. 4,32 However, it is noted that at the bottom of the talar head, the mean shape of the female tali extrudes which means that its talar head has a large top-bottom thickness and is therefore more plantar flexed. Therefore, we do not consider the average female shape to be geometrically similar to the average male shape as Liu et al 29 claimed.…”
Section: Discussionmentioning
confidence: 99%
“…3,713 The shape variability of the talus within specific populations is important for accurate diagnosis, treatment planning, and implant design. 3,4,1417…”
Section: Introductionmentioning
confidence: 99%
“…3,8,11 However, Inman's hypothesis and the basis for this design has been challenged by later studies, which suggest that the Salto Talaris has incongruence between talar and polyethylene components. 9,11,14,17 In contrast to the Salto Talaris, the design of INBONE II is based on the 2-sphere fitting model that is purported to closely approximate the talar trochlea, 17 with improved stability from the first generation of the INBONE (Supplemental Figure S1). 13 We assume that the designs for each implant may explain the major differences in reoperation rates between 2 groups, but we must also acknowledge that other factors, such as implant or polyethylene size, varus or valgus thrust from hindfoot malalignment, and the adequacy of prophylactic resection depending on the surgeon, may have influenced the outcomes in each group.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,11 However, Inman’s hypothesis and the basis for this design has been challenged by later studies, which suggest that the Salto Talaris has incongruence between talar and polyethylene components. 9,11,14,17…”
Section: Discussionmentioning
confidence: 99%
“…The TTR customisation procedure was mimicked by reconstructing a model part of the talar prosthesis from the mirror image data of the contralateral ankle site, which is a common practice in clinical studies in the related field [ 12 , 14 , 21 ]. Because a growing body of evidence indicated that a prosthesis design with a higher approximation to the native ankle anatomy facilitates the restoration of ankle functions [ [21] , [22] , [23] ], we hypothesised that TTR would better reproduce the foot kinematics and force distribution of an intact foot than would TAA. TTR improved ankle motions and reduced foot arch deformation/loadings to the foot segments compared to TAA.…”
Section: Introductionmentioning
confidence: 99%